Delay Normalization Technique to Disrupt Covert Timing Channels Using Active Warden - Uttarwar Vrushali Uday; Dakhane Dhananjay M. (EPJ Web of Conferences)
Covert channels exploit existing network resources, such as packet headers and timing information, to transfer information in ways not originally intended for communication, making them undetectable by conventional methods. This poses significant security risks, as these channels can be used maliciously despite stringent security measures like firewalls. Hence, there is a critical need for a generalized mechanism capable of blindly detecting covert communications within network traffic. We have developed a framework to evaluate covert timing channels and conducted experiments with an active warden. Our findings indicate that the active warden effectively prevents covert timing communication, demonstrating the framework's potential for enhancing network security.